Paradoxart - Schaefer, Claudia; Galerie Cubus, Duisburg (Duisburg : Galerie Cubus, 1989)
Balili, Mbarek ; Begasse, Hubert ; Bhar, Abdelhamid ; Chemao, Nacir ; Grundei, Claudia ; Horsch, Robin ; Laftouhi, Abdelaziz ; Lipka, Wolf-D.
Paradoxart, Galerie Cubus, Duisburg, 1989
boek
Keywords: Marokko